10. CULTIVATING THE CULTURE OF ISLAMIC NATION: A LIVING EXAMPLE OF PROPHET MUHAMMAD’S INTEGRITY - Zainan Nazri, Nurul Mukminah; Zainan Nazri, Nurul Jannah; Nazri, Mohd Arif (Journal of Islamic, Social, Economics and Development, 2024)
This study scrutinizes the concept of integrity and various dimensions of integrity in human life, with a specific focus on the journey of Prophet Muhammad as a living example. The topic of integrity has been discussed due to its association with the predicaments of corruption and bribery. Numerous studies have established that a deficiency in integrity is identified as a contributing factor to corrupt practices. The approach employed in this qualitative study is content analysis. Data collected through content analysis are thematically analyzed using descriptive and analytical methods. Findings demonstrate that Prophet Muhammad was a man full of integrity throughout his life as a wage earner, Allah’s messenger and leader. Thus, the implications validate the notion that Prophet Muhammad serves as a quintessential exemplar for humanity. Consequently, through a reflective exploration of the life journey of Prophet Muhammad, valuable insights can be derived to combat the problem of corruption and bribery.